2016
DOI: 10.1080/02660830.2016.1155850
|View full text |Cite
|
Sign up to set email alerts
|

Navigating our way: A compass for popular educators

Abstract: This article addresses the tensions and contradictions of applying a popular education approach in the current context of South Africa. It draws upon data from an eighteen month research project into traditions of popular education. It presents an extended discussion on the meanings of popular education, and their varied implications for practice. It presents a heuristic device in the form of a `compass`, to assist popular educators locate themselves in their work at different historical moments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Despite the sample size, our results cannot be generalizable, since nation-related samples are not generalizable. Second, while liberal adult education could be empowering, its emancipatory benefits are questionable, since an empowered self can fail to use its empowerment to help others through collective change (Von Kotze et al, 2016). In fact, many critical educational gerontology studies have reported occasions where even critical education did not fully lead to emancipation (see, for example, Formosa, 2012;Formosa & Galea, 2020;Nye, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the sample size, our results cannot be generalizable, since nation-related samples are not generalizable. Second, while liberal adult education could be empowering, its emancipatory benefits are questionable, since an empowered self can fail to use its empowerment to help others through collective change (Von Kotze et al, 2016). In fact, many critical educational gerontology studies have reported occasions where even critical education did not fully lead to emancipation (see, for example, Formosa, 2012;Formosa & Galea, 2020;Nye, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…There are intersections between popular education and emancipatory education when understanding education as a tool for change. Popular education or non-formal initiatives of education often develop when groups are excluded from formal education systems, where movements take it upon themselves to become educators (von Kotze, Walters & Luckett 2016). Popular educators often emphasise the pedagogy used in popular education as different from the pedagogy used in formal education systems.…”
Section: Formative and Mobilising Educationmentioning
confidence: 99%
“…Like Paulo Freire's praxis, educational activists, at best, combine sound theoretical and ethical reflection with empathetic critical action. Popular education, which is rooted in the radical tradition of adult education and grounded in the philosophy of Paulo Freire, is overtly political, concerned with people's experiences, and orientated towards action (von Kotze et al, 2016). Its purpose is the collective production of "really useful knowledge" which is tested when translated into action.…”
Section: Introductionmentioning
confidence: 99%
“…While feminist popular education is embedded within socio-economic and environmental contexts, it was only during the drought of 2017/18 that I began to focus more intentionally on what the climate crisis means and to question how we as adult popular educators should respond. I wrote (Walters, 2018) of "the drought as my teacher", as we individually and collectively rethought our relationship to water. The crisis, as with many crises, heightened awareness of the inequalities in society and, in particular, of water injustice.…”
Section: Introductionmentioning
confidence: 99%